Measurements of Orbital Protrusion From Childhood to Young Adulthood. Issue 3 (May 2015) - Meazzini, Maria Costanza; Miccoli, Cosimo; Fastuca, Rosamaria; Panzi, Silvia; Mangano, Francesco; Mortellaro, Carmen; Caprioglio, Alberto
<x xml:space="preserve">Abstract</x> Background: Ocular protrusion is usually measured as the deepest part of the lateral orbital rim to the apex of the cornea. Several studies have been carried out to propose normative data for ocular protrusion according to different age ranges. The protrusion of the eyeball seemed to increase during childhood and adolescence and become stable after the late teens during adulthood. Relationships of ocular protrusion with age are still not completely clarified. The purpose of the current retrospective study was to investigate ocular protrusion on lateral x-rays at different growth stages. Methods: Ninety-five patients were retrospectively selected and divided into 5 different groups according to ages. Subjects were of both sexes with an age range from 5 to 20 years (mean 12.3 years). The cephalometric analysis proposed in the current study allowed to successfully evaluate sagittal relationships of the orbital-globe and the orbital-cavity in growing patients. All other sagittal and vertical measurements were successfully computed by one trained operator. Results: Analysis of variance results with post hoc corrections showed for the orbital measurements indicating a significant increase of the orbital protrusion from childhood to pubertal stage. Conclusions: Ocular protrusion measurements showed significant increase from childhood (5–8 years) to teen age (13–15 years) and remained stable after the pubertal growth spurt (17–20 years) in the examined sample of patients.